Detectors for Registration of Electron Radiation Fluxes in Near- Earth Space - Bazaleev, M. I.; Evseev, I. G.; Klepikov, V. F.; Litvinenko, V. V.; Shevchenko, M. G. (Видавничий дім «Академперіодика», 2012)
Detectors for Registration of Electron Radiation Fluxes in Near- Earth Space